PENDAMPINGAN PENERAPAN SISTEM JAMINAN PRODUK HALAL PADA UMKM OMAH KUE UTI ATIK DI KOTA BALIKPAPAN - Khansa Fitria Latifa Hidayat; Anton Rahmadi; Marwati Marwati; Miftakhur Rohmah (LPPM Universitas Bina Bangsa, 2022)
Indonesia requires halal certification which is regulated in Law Number 33 of 2014 concerning Guaranteed Halal Products. Making halal certificates for micro and small businesses can be done in two ways, namely through the regular mechanism and the self-declare mechanism. This activity aims to increase empathy and concern for students, so that they can contribute to developing Omah Kue Uti Atik UMKM in Balikpapan City through socialization so that the quality of the products produced is guaranteed and can survive among the many similar products being traded. The implementation method used in this activity has three stages, namely the preparation stage by conducting a survey of the conditions and needs of MSMEs. The implementation stage, namely by conducting outreach to MSMEs by providing information and education. The implementation stage, namely by assisting in the preparation of SJPH documents and the process of registering a Self-Declared halal certificate. From the results of the service, MSME actors know the importance of producing halal products, fulfilling certification criteria and obtaining halal certificates through self-declaring